Personal space increases during the COVID-19 pandemic in response to real and virtual humans - Holt, Daphne J.; Zapetis, Sarah L.; Babadi, Baktash; Zimmerman, Jordan; Tootell, Roger B. H. (Frontiers in Psychology, 2022)
Personal space is the distance that people tend to maintain from others during daily life in a largely unconscious manner. For humans, personal space-related behaviors represent one form of non-verbal social communication, similar to facial expressions and eye contact. Given that the changes in social behavior and experiences that occurred during the COVID-19 pandemic, including “social distancing” and widespread social isolation, may have altered personal space preferences, we investigated this possibility in two independent samples. First, we compared the size of personal space measured before the onset of the pandemic to its size during the pandemic in separate groups of subjects. Personal space size was significantly larger in those assessed during (compared to those assessed before) the onset of the pandemic (all d > .613, all p < .007). In an additional cohort, we measured personal space size, and discomfort in response to intrusions into personal space, longitudinally both before and during the pandemic, using both conventional and virtual reality-based techniques. Within these subjects, we found that measurements of personal space size with respect to real versus virtual humans were significantly correlated with one another (r = .625-.958) and similar in magnitude. Moreover, the size of personal space, as well as levels of discomfort during personal space intrusions, increased significantly during (compared to before) the COVID-19 pandemic within these subjects, in response to both real and virtual humans (all d > .842, all p < .01). Lastly, we found that the practice of social distancing and perceived (but not actual) risk of being infected with COVID-19 were linked to this personal space enlargement during the pandemic (all p < .038). Taken together, these findings suggest that personal space boundaries expanded during the COVID-19 pandemic independent of actual infection risk level. As the day-to-day effects of the pandemic subside, personal space preferences measured with respect to real or virtual humans may provide one index of recovery from the psychological effects of this crisis.